2003
DOI: 10.1002/app.13138
|View full text |Cite
|
Sign up to set email alerts
|

New polymeric Schiff base and its metal complexes

Abstract: A novel polymeric Schiff base was synthesized by the reaction of a Schiff base from 2,4-dihydroxy benzaldehyde and aniline with acryloyl chloride and was polymerized in methyl ethyl ketone at 70°C with benzoyl peroxide as a free-radical initiator. Polychelates were obtained in an alkaline solution of poly(2-hydroxy-4-acryloyloxy-N-phenylbenzylidine) with aqueous solutions of metal ions such as Cu(II), Ni(II), Co(II), Ca(II), Cd(II), Mn(II), and Zn(II). The polymeric Schiff base and polychelates were characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…All the complexes are insoluble in water and fusible at higher temperatures and are polymeric in nature [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…All the complexes are insoluble in water and fusible at higher temperatures and are polymeric in nature [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…It is found that the E a values parallel the thermal stability. The negative value obtained for the entropy change (Δ S ) and the low value of frequency factor ( Z ) suggest that both the oligomeric ligand and its metal complexes undergo a slow degradation reaction , . The order of the reaction for all the compounds is nearly one.…”
Section: Resultsmentioning
confidence: 93%
“…The oligomer–metal complexes have a more close‐packed structure than the ligand. Generally, insertion of metal ions into a polymeric lattice increases the crystallinity . The appearance of increased crystallinity in the case of the metal complexes may be due to the inherent crystalline nature of the metals.…”
Section: Resultsmentioning
confidence: 99%
“…[17][18][19] Another interesting property of these polymeric materials is their complex-forming ability with transition metal ions, exhibiting a wide variation in electrical and magnetic characteristics. [20,21] Some of polyazomethines exhibit thermotropic liquid crystal behavior [15,22] due to having mainly azomethine linkages in the backbone and they can be used to obtain high performances fibers. [23] However these materials have some drawbacks (or advantages depending on the type of applications) such as low solubility in organic solvents and high melting temperatures.…”
Section: Introductionmentioning
confidence: 99%